Impacts of Birth Weight on Plasma, Liver and Skeletal Muscle Neutral Amino Acid Profiles and Intestinal Amino Acid Transporters in Suckling Huanjiang Mini-Piglets - Yang, Huansheng (Public Library of Science, 2012)
Genetic selection strategies towards increased prolificacy have resulted in more and more increased littler size and incidences of impaired fetal development. Low birth weight (LBW) piglets, with long-term alterations in structure, physiology and metabolism, have lower survival rates and poor growth performance. The aim of the study was to compare the plasma, liver and skeletal muscle contents of neutral amino acids (NAA) and the intestinal expression of NAA transporters between LBW and high birth weight (HBW) suckling Huanjiang mini-piglets. Forty piglets with either LBW or HBW (20 piglets per group) were sampled on day 0, 7, 14 and 21 of age to give 5 observations per day per group. The contents of NAA in plasma, liver and skeletal muscle were measured, and jejunal expression of transporters for NAA, including Slc6a19 (B(0)AT1) and Slc1a5 (ASCT2), were determined by real-time RT-PCR and Western Blot, respectively. Results showed that the suckling piglets with LBW had higher contents of Thr, Ser, Gly, Ala, Val, Met, Ile, Leu, Tyr, Phe and Pro in liver, and Gly in skeletal muscle, whereas lower contents of Met, Ser and Ala in plasma when compared with the HBW littermates. Consistent with the content differences in plasma NAA, the jejunal expression profiles of both Slc6a19 (B(0)AT1) and Slc1a5 (ASCT2) in the LBW piglets were lower in compared with the HBW littermates during the early suckling period. These findings suggested that intestinal dysfunction in the LBW piglets may be one of the reasons in altered physiology and metabolism states of other organs, which result in lower survival and growth rate.